IRIS – An Internet Based Intervention as a Suitable Path to Addictive Substance Use Prevention and Counselling in Pregnancy? Beneficiary Profiles and User Satisfaction - Stiegler, A.; Abele, H.; Batra, A. (Geburtshilfe und Frauenheilkunde, 2016)
Alcohol or tobacco consumption in pregnancy can harm the unborn child. Counselling on this subject is therefore of major importance. The aim of the presented study was not only to develop an internet based, professionally e-mail accompanied platform for alcohol or tobacco consuming pregnant women (“IRIS Platform”) but also to analyse the beneficiary profiles and investigate the practicability and acceptance of the platform among women and referring gynaecologists. The offer comprised three 12-week counselling programmes (alcohol, tobacco, combined consumption). Altogether 32 women registered within the recruitment period of 20 weeks, only 9 of them at the suggestion of gynaecologists. Thirty were enrolled. The average age was 31 years. Ten women were pregnant for the first time, 14 unplanned. Most of them were smokers (n = 29). 75 % (n = 12 of 16) of them had smoked in the previous pregnancies, 5 of 16 women had suffered miscarriages. Six women completed the entire 12 week programme. The abstinence rate after 3 months was min. 18.5 % (ITT) in the tobacco group, while in the alcohol programme 3 women achieved abstinence. Satisfaction was reported especially for the eCoach initiative. The results demonstrate that an internet-based service like IRIS can be a useful form of support for tobacco or alcohol consuming pregnant women. A particular challenge is the accessibility of the persons concerned and the form in which alcohol consuming pregnant women are approached in daily medical practice. The individual contact to the eCoach can be a decisive form of support and aid to motivation.
Keywords: pregnancy; alcohol; tobacco; internet; prenatal prevention